Accuracy Of Fine Needle Aspiration Cytology (FNAC) In The Diagnosis Of Thyroid Swellings (Journal of Dhaka National Medical College & Hospital, 2013)
Objective: To evaluate the accuracy of fine needle aspiration cytology (FNAC) in comparison to paraffin section in thyroid swelling. Study design: Cross sectional study. Place and duration of study: Department of Surgery, Bangabandhu Sheikh Mujib Medical University from July 2009 to June 2011. Patient and method: One hundred patients with enlarged thyroid gland of both sexes were selected from admitted patient of Surgery department. All patients had preoperative FNAC, performed by pathologist at the Histopathology department and postoperative specimen were also examined and histopathological diagnosis were made. All FNAC diagnosis were correlated with the histopathological diagnosis. Results: Out of 100 patients 23 were male and 77 were female, male-female ratio 1: 3.3. In FNAC 76 patients were diagnosed as benign lesion of which 8 were later diagnosed as malignant on histopathological examination (68 were true negative 8 were false negative). 22 cases were diagnosed as malignant, both on FNAC and histopathological examination. Only 2 cases were diagnosed as follicular neoplasm on FNAC but on histopathological examination diagnosed as follicular carcinoma (22 cases were true positive) in this study. Overall sensitivity of FNAC were 68.75%, specificity 100.00% and accuracy 90%; PPV=100% & NPV=87.18% Conclusion: FNAC is a reliable, safe and accurate method as a preoperative evaluation in thyroid gland swelling before surgery. FNAC has more accuracy and specificity in detecting thyroid gland malignancy and therefore it is a reliable diagnostic test for evaluating thyroid swellings. DOI: http://dx.doi.org/10.3329/jdnmch.v18i2.16023 J. Dhaka National Med. Coll. Hos. 2012; 18 (02): 47-51